Oral Realgar-Indigo Naturalis Formula Plus Retinoic Acid for Acute Promyelocytic Leukemia - Lou, Yinjun; Ma, Yafang; Jin, Jie; Zhu, Honghu (Frontiers in Oncology, 2021)
Treatment paradigm of acute promyelocytic leukemia (APL) is by no mean the most remarkable story of cancer therapy. Recently, the advent of oral arsenic formulations (oral-arsenic trioxide and Realgar-Indigo Naturalis formula (RIF)) based regimens may provide a therapeutic advance by curing APL with two oral agents. Indeed, the oral RIF plus all-trans-retinoic acid (ATRA) without chemotherapy display highly efficacy in patients with APL. The safety profile of RIF plus ATRA make possible to treat APL patients in a home-based manner during postremission therapy. To our knowledge, RIF was the first commercially available oral arsenic agent approved in China. The RIF plus ATRA regimens are becoming a preferred frontline care for APL in China. In this review, we will discuss the history, current evidences and challengers of RIF-based strategies in APL. More and more APL patients may enjoy a cure with a normal quality-of-life after induction in the near future.